(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2015)
Museums in Malaysia, including those in the northern region, have become closely associated with nation building seeking to project commonly shared experiences besides their increasing attachment to the tourism industry. The cultural displays in these museums are done in line with the national culture policy that favours Malay and other indigenous cultures that were not contradictory to Islamic precepts. This essay scrutinises 28 general and specialised museums located in the northern region of peninsula Malaysia, covering the states of Perlis, Kedah, Penang and northern Perak. These museums are under the administration of the Department of Museums, state governments and other government departments, besides private organisations and individuals. A few of the more important ones are discussed in details while the natures of their main exhibits are tabulated for easy reference. The discussion looks at the visitor numbers to these museums and provides possible reasons for museum attractions to visitors. The more substantiated discussion focuses on the region's distinctive performing arts like boria, mek mulong, hadrah, the cultural side of the Perak Man and paddy cultivation, and Chinese Peranakan culture in the museums.